THE ROLE OF NOTARY IN DEED OF SALE AND PURCHACE AGREEMENT TO SUPPORT NATIONAL DEVELOPMENT - hasyim mustofa (Jurnal Pembaharuan Hukum, 2017)
Notary's duty is as a legal profession carrier in the making of Land sale and purchase Deed as a perfect proof. However, the Notary in carrying out his duties and authorities must pay attention to the formal and material aspects. In this case, there are some constraints such as the status of land and the Notary is not authorized to run a Position outside his/her position. Method approach used in this study was normative juridical, where the data source comes from secondary data, consisting of primary, secondary and tertiary legal materials. The results of the research found that the role of notary in making the deed of land purchase agreement to support the national development rests with the legal relationship to bind the parties' engagement in the form of the PPJB (Sale and Purchase Binding Agreement) deed which can be used as the perfect evidence when one of the parties pledges through the lawsuit in the court. As well as obstacles in making the Deed PPJB include land status, such the status of customary land, State land and land letter C so as to violate the object of agreement as regulated in Article 1320 Civil Code. Furthermore, the unauthorized acts are as referred to in Article 85 of the Notary Position Law.